PELATIHAN PEMBUATAN AWETAN KERING RESIN DAN INSEKTARIUM BAGI CALON GURU BIOLOGI : Training in Making Resin Dry Preserves and Insektarium for Prospective Biology Teachers - Indriyani, Sari; Himmah, Nurul; Norfajrina (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2024)
Abstract: The training on resin dry preservation and insektarium making at UIN Antasari Banjarmasin prioritises the development of participants' practical skills and conceptual understanding with detailed knowledge that is then applied in practice to create quality results according to the educational curriculum. An evaluation was organised to provide constructive feedback, encouraging participants to improve their skills and understanding of the importance of these techniques in the context of biology education. The training involved participants from prospective biology teachers, namely 4th and 6th semester students in the Biology Education Study Programme. The activity began with a presentation that provided an initial understanding of the materials, tools, and benefits of the preservation techniques, followed by the stages of making which were explained in detail. After that, participants practised hands-on practice in making preserves. The results of the training were given to the Integrated Laboratory of Technology of UIN Antasari Banjarmasin as a learning resource for prospective biology teachers. Evaluation was conducted to assess the accuracy of the steps and the quality of the work, and to provide suggestions for improvement. Thus, this training is expected to improve biology education in various schools by making a positive contribution to prospective biology teachers.  Keywords: Dry Preservation; Teacher Candidate; Insektarium; Training; Resin.   Abstrak: Pelatihan pembuatan awetan kering resin dan insektarium di UIN Antasari Banjarmasin dengan mengedepankan pengembangan kemampuan praktis dan pemahaman konseptual peserta dengan pengetahuan detail yang kemudian diterapkan dalam praktik untuk menciptakan hasil berkualitas sesuai kurikulum pendidikan. Evaluasi diselenggarakan untuk memberikan umpan balik yang konstruktif, mendorong peserta untuk meningkatkan keterampilan dan pemahaman mereka terhadap pentingnya teknik tersebut dalam konteks pendidikan biologi. Pelatihan melibatkan peserta dari calon guru biologi, yaitu mahasiswa semester 4 dan 6 di Program Studi Pendidikan Biologi. Kegiatan dimulai dengan presentasi yang memberikan pemahaman awal tentang bahan, alat, dan manfaat teknik pembuatan awetan, dilanjutkan dengan tahapan pembuatan yang dijelaskan secara rinci. Setelah itu, peserta berlatih praktik langsung dalam pembuatan awetan. Hasil pelatihan diberikan kepada Laboratorium Terpadu Sainteknologi UIN Antasari Banjarmasin sebagai sumber belajar bagi calon guru biologi. Evaluasi dilakukan untuk menilai ketepatan langkah-langkah pembuatan dan kualitas hasil karya, serta memberikan saran untuk peningkatan. Dengan demikian, pelatihan ini diharapkan dapat meningkatkan pendidikan biologi di berbagai sekolah dengan memberikan kontribusi positif pada calon guru biologi. Kata kunci: Awetan Kering; Calon Guru; Insektarium; Pelatihan; Resin.